2017
DOI: 10.5194/isprs-annals-iv-1-w1-107-2017
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Extract Moving Objects From MLS Data Using a Volumetric Background Representation

Abstract: ABSTRACT:Data recorded by mobile LiDAR systems (MLS) can be used for the generation and refinement of city models or for the automatic detection of long-term changes in the public road space. Since for this task only static structures are of interest, all mobile objects need to be removed. This work presents a straightforward but powerful approach to remove the subclass of moving objects. A probabilistic volumetric representation is utilized to separate MLS measurements recorded by a Velodyne HDL-64E into mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 10 publications
(13 reference statements)
0
43
0
Order By: Relevance
“…1a, we provide an overview of the entire scene. To some extent, this scene is a representative scenario of the urban area, including rich information of buildings, vehicles, vegetations, ground surfaces, et al Here, the basic point cloud is original acquired by Fraunhofer Institute of Optronics, System Technologies and Image Exploitation (IOSB) (Gehrung et al, 2017). The utilized point clouds are acquired by two Velodyne HDL-64E mounted with an angle of 35…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a, we provide an overview of the entire scene. To some extent, this scene is a representative scenario of the urban area, including rich information of buildings, vehicles, vegetations, ground surfaces, et al Here, the basic point cloud is original acquired by Fraunhofer Institute of Optronics, System Technologies and Image Exploitation (IOSB) (Gehrung et al, 2017). The utilized point clouds are acquired by two Velodyne HDL-64E mounted with an angle of 35…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 5 provides sketch about how the two scanners are mounted (Gehrung et al, 2017). The original raw point clouds are also preprocessed by a statistical outlier removal for down-sampling and noise suppressing.…”
Section: Resultsmentioning
confidence: 99%
“…A voxel list updated by conflict search between the known environment and LiDAR measurements is clustered and filtered for object candidates. The theoretical framework behind Octomap has also been used in our previous works, where we showed that the classification of voxels based on voxel statistics leads to the artifacts mentioned above and therefore to an inaccurate approximation of the environment (Gehrung et al, 2016(Gehrung et al, , 2017.…”
Section: Change Detection Using Occupancy Gridsmentioning
confidence: 99%
“…This leads to conflicting observations and therefore to large patches of incorrectly classified voxels. We showed in (Gehrung et al, 2017) that this effect appears when determining the voxel class on volume statistics only, without including information of higher levels such as the local neighborhood (cf. Figure 1(b)).…”
Section: Discretization Based Artifactsmentioning
confidence: 99%
“…This representation leads to a fast segmentation but it might fail when the scale of the objects in the scene is too different. Gehrung et al (2017) propose to extract moving objects from MLS data by using a probabilistic volumetric representation of the MLS data in order to cluster points between mobile objects and static objects. However this technique can only be used with 3D sensors.…”
mentioning
confidence: 99%